Rooted in Culture, Grounded in Faith: Narrative Accounts of Acehnese Ethnopedagogy as a Framework for Culturally Responsive Islamic Religious Education - Fauzan Fauzan; Habiburrahim Habiburrahim; Mumtazul Fikri; Nizar Saputra; Zainul Mujtahid (International Journal of Educational Narratives, 2026)
Background. Islamic Religious Education (IRE) learning in higher education tends to be theoretical and has not fully integrated local wisdom, particularly Acehnese culture, resulting in less contextual learning and low student engagement and understanding. In addition, the lack of ethnopedagogy-based learning tools becomes an obstacle in creating integrative and meaningful learning. Purpose. This study aims to develop ethnopedagogy-based IRE learning tools grounded in Acehnese local wisdom and to examine their validity, practicality, and effectiveness in improving students’ understanding and internalization of Islamic values. Method. This research employed a Research and Development (R&D) approach using the ADDIE model, which includes Analysis, Design, Development, Implementation, and Evaluation stages. This study involved 35 respondents in the product testing and implementation phases: three lecturers, 30 university students, and two Acehnese cultural practitioners. Product validation involved nine experts: three in Islamic Religious Education content, three in instructional media, and three in Acehnese culture. Overall, 44 participants were involved in the validation, testing, and implementation phases. Results.The study confirmed a strong need for Acehnese ethnopedagogy-based Islamic Religious Education materials among lecturers (88.3%) and students (82.2%). Developed through the ADDIE model, the materials were valid, highly practical for lecturers (92%) and students (92.8%), and effectively implemented (79%). Their effectiveness was reflected in the increase from a 57.2 pretest mean to an 81.6 posttest mean and an 88.05% student response, indicating improved understanding of Islamic values and appreciation of Acehnese culture. Conclusion. Ethnopedagogy-based IRE learning tools rooted in Acehnese local wisdom are proven to be feasible and effective in improving the overall quality of learning. The integration of local wisdom makes learning more contextual, meaningful, and relevant to students’ lives.